P178 Clinician And Patient Experience In The Delivery Of A Day-case Local Anaesthetic Thoracoscopy Service At A Specialist Pleural Unit. (10th November 2014) - Psallidas, I; Corcoran, JP; Hallifax, RJ; Talwar, A; Sykes, A; Rahman, NM
Abstract : Background and method: Local anaesthetic thoracoscopy (LAT) is utilised by an increasing number of respiratory physicians for diagnostic and therapeutic purposes in the setting of pleural disease. Although guidelines [1] allow for day-case LAT (i.e. procedure and discharge home on the same day), the majority of UK centres electively admit patients for overnight observation post-procedure. This impacts on service provision by increasing bed occupancy and limiting procedural capacity; whilst affecting patients by incurring a hospital stay they might not need. Reasons for centres not offering day-case LAT are unclear but may include clinician experience and limitations in the available guidelines. Day-case LAT has been offered by our tertiary centre-based pleural service for a number of years. Patients are routinely considered for this approach if their procedure is for purely diagnostic purposes, as opposed to being therapeutic in addition (i.e. whether talc poudrage pleurodesis is anticipated). Other factors considered in the decision-making process include performance status, co-morbidities and social background. A review of our procedural database from January 2010 to June 2014 was performed to identify the number of day-case LATs and define the characteristics of the patient population offered this approach. Results: Of 294 LATs booked during this period, 127 (43.2%) were planned as a day-case procedure. 113 day-case LATs went ahead with 7 patients (6.2%) requiring an "unplanned" hospital admission for reasons outlined in Figure 1 . Patients planned for day-case LAT tended to be younger (68.1 vs. 72.4 years, p = 0.12, unpaired t-test) with fewer co-morbidities and better social support than the general population having this procedure. No patient declined a day-case procedure having been offered one, whilst the process on the day proved acceptable with most patients valuing the opportunity to avoid an overnight hospital stay. Conclusion: With careful case selection day-case LAT can be provided successfully, benefiting patients and clinicians whilst saving bed days and healthcare costs. Centres with the appropriate case mix and experience may wish to develop day-case LAT as part of their service. Future guidelines should acknowledge this need and offer advice on patient selection and logistical requirements. Reference: Thorax 2010; 65 Suppl 2:ii54–60